Biotechnological approaches for enhancing the resistance of tomato plants to phytopathogenic bacteria - A. Buziashvili; Y. Kolomiiets; L. Butsenko; A. Yemets (Biologia Plantarum, 2023)
Bacterial diseases of vegetable crops cause significant losses of yield and substantially decrease food quality. For sustainable development of agriculture, it is highly important to use the most effective strategies for the protection of vegetable crops from bacterial diseases which allows the creation of resistant cultivars and their introduction in regions with an increased risk of damage by phytopathogenic bacteria. This paper reviews the most widespread bacterial diseases of tomatoes, the mechanisms of interaction of plants with phytopathogenic bacteria, and the advantages of the biotechnological strategies over traditional and marker-associated breeding for creation of the resistant tomato cultivars. The current research progress on the use of biotechnological approaches such as cell selection, genetic engineering, genome editing, and gene silencing is summarized, with a special emphasis on the advantages and limitations of these methods.